A Reflection of “Indonesian Maritime Fulcrum” Initiative: Maritime History and Geopolitical Changes - Ismail Ali; Singgih Tri Sulistiyono (Journal of Maritime Studies and National Integration, 2020)
The announcement of a maritime economic initiative known as the 21st Century Maritime Silk Route (MSR) by Chinese President Xi Jinping in 2013 created a new paradigm shift in the geo-economy and geo-politics of countries in the Pacific Ocean and Indian Ocean. With this initiative, China aims to rebuild maritime lines in the seas and oceans where China once was regarded as one of the world's leading powers. In contrast to countries in Southeast Asia, which still hold divergent views on the Chinese initiative, Indonesia sees it as an opportunity to develop regions that have long been marginalized from development. It is in line with the shift in Indonesia’s global economic-political agenda in the 21st century through a doctrine known as "Indonesia as a Maritime Fulcrum," which was initiated by “Jokowi” Widodo and Jusuf Kalla in 2014. Taking into account the importance of this idea in Indonesia's geo-economic and geo-political agenda, this study is to reflect on Indonesia’s history as a global maritime and trade power before it was undermined by the Dutch occupation. In addition, using historical approach, this study aims to see and evaluate how the idea of "Indonesia as a Maritime Fulcrum" can restore Indonesia’s reputation as a major maritime power in the Southeast Asian archipelago.